Further dicentric X isochromosomes and deletions, and a new structure i(X)(pter to q2102 to pter). Issue 4 (August 1979) - Daniel, A; Saville, T; Southall, D B
Abstract : A new dicentric X isochromosome i(X)(pter to q2102 to pter) of similar size to a normal X is described in a girl with gonadal dysgenesis. In this non-mosaic case with an X short arm duplication, most of the stigmata associated with Turner's syndrome were absent. This structure was compared with that of six i(Xq) and three del(X). The del(Xq) structures all possessed a regular sized C band, but in the i(Xq) this was double sized in each case. Phenotypic comparisons are made in the Xq deletions, and some presumptive short arm isochromosomes are reinterpreted as Xq deletions. Incomplete centromeric suppression is suggested as the causal mechanism of mosaicism of sex isochromosomes with 45, X cells, and it is argued that an exchange event between homologoues is an unlikely mechanism to explain sex isochromosome origin.